2012
DOI: 10.1038/onc.2012.434
|View full text |Cite
|
Sign up to set email alerts
|

Lactotransferrin acts as a tumor suppressor in nasopharyngeal carcinoma by repressing AKT through multiple mechanisms

Abstract: LTF (lactotransferrin, also known as lactoferrin) is a key component of innate immune defense. It has recently been found to have anti-tumor and anti-metastatic activity in different cancers. We previously reported LTF to be the most significantly downregulated gene in nasopharyngeal carcinoma (NPC) specimens relative to normal nasopharyngeal epithelial tissues, and it was also negatively associated with the progression and metastasis of NPC. However, the mechanism underlying this remains unclear. In the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 44 publications
3
61
0
Order By: Relevance
“…Consistent with IPA results, DAVID analysis also indicated an enrichment of genes associated with inflammatory response, complement activation and osteogenic differentiation (Supplementary Table 2). The 99 genes down-regulated in common included LTF, a tumor suppressor and inhibitor of AKT signaling [18], and PDCD4, a tumor suppressor gene whose decreased expression has been implicated in the development and progression of several types of cancer [19][20][21][22].…”
Section: Bm-msc Exposed To Leukemia In Vivo Show Changes In Their Genmentioning
confidence: 99%
“…Consistent with IPA results, DAVID analysis also indicated an enrichment of genes associated with inflammatory response, complement activation and osteogenic differentiation (Supplementary Table 2). The 99 genes down-regulated in common included LTF, a tumor suppressor and inhibitor of AKT signaling [18], and PDCD4, a tumor suppressor gene whose decreased expression has been implicated in the development and progression of several types of cancer [19][20][21][22].…”
Section: Bm-msc Exposed To Leukemia In Vivo Show Changes In Their Genmentioning
confidence: 99%
“…Our subsequent studies showed that LF inhibits NPC cell proliferation, induces cell cycle G 1 /S arrest, modulating MAPK signaling pathway, and cyclin D1-related proteins, 20 and inhibits NPC metastasis by suppressing AKT activity. 25 EBV is widespread in human populations, and EBV infection has been linked to the tumorigenesis of multiple cancers including NPC. 1 One important consequence of EBV infection is malignant transformation of epithelial cells, promoted by EBV-encoded protein and microRNAs.…”
Section: Lf Expression Levels Correlated Inversely With Mcp-1 and Il-mentioning
confidence: 99%
“…The full-length LTF coding sequence entirely lacking the 3'-UTR (GeneCopoeia, Rockville, MD, USA) was subcloned into the eukaryotic expression vector pIRES (Clontech Laboratories, Inc., Mountainview, CA, USA) as previously described (20). The fusion sequences were verified by DNA sequencing using a Sanger ABI 3730xl DNA sequencer (GATC Biotech AG, Konstanz, Germany).…”
Section: Construction Of the Pires-ltf Vectormentioning
confidence: 99%